Sex-specific analysis of individual and ski geometry-related risk factors for ACL injuries in recreational alpine skiing: A case-control study - Gerhard Ruedl; Martin Faulhaber; Markus Posch (Current Issues in Sport Science)
Introduction In recreational alpine skiing, female skiers experience knee injuries at twice the rate of male skiers, with the risk of anterior cruciate ligament (ACL) injuries being three times higher in women (Posch et al. 2021). In addition to individual factors such as, e.g., age or skill level, ski geometry parameters may also influence the risk of ACL injuries (Ruedl et al., 2022). Therefore, the aim of this study was to assess sex-specific effects of individual factors and ski geometry parameters on ACL injury risk in recreational skiers.